MODERASI PROFITABILITAS PADA PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN - Maria Katharina Sare (JURNAL AKUNTANSI, 2022)
Taxes for a company are a burden that can reduce corporate profits, while taxes for a country are an income that will be used to cover state expenses. These differences lead companies to tax liability management. Frequent action is a tax avoidance. By performing a tax avoidance company capable of optimizing profits and can attract investors because of their high value. Corporate values are also affected by high corporate profitability. The theories underlying this research are agency theories and signal theories. The population of this study is 14 multinational companies registered to the Indonesia stock exchange in 2017-2021, making up 70 samples of the company. The data analysis techniques used are descriptive, pooling, classic assumptions test, simple linear regression analysis tests, moderated regression analysis (MRA), test f, test t and r2. Data obtained from (www.idx. Co. id) and (www.idnfinancials). As well as other sources (www.yahoofininance.com). The study shows that tax avoidance has an impact on corporate value, and moderating profitability has proven to strengthen the impact of tax avoidance on corporate values.